No Hero Here! (A Post Colonial Study on Bahurekso Story) - Susanto Susanto (Universitas Muhammadiyah Semarang, 2017)
Bahurekso, one of Pekalongan`s folktales and local wisdoms, is promoted to be taught in school. However, not all folktales can be taught to students. Like literary work, Folktale needs to be read critically.In this paper, Bahurekso was analyzed from the perspective of post colonialism. The aim of this research was to find colonial values or ideologies contained in the story. The data were collected through library research by collecting supported data from journals, books and other related sources.The result of the study showed that Bahurekso story contained colonial values in form of representation of Baurekso as coward, traitor, and deceitful hero. In fact, Bahurekso isMataram commander who died in Battle of Batavia to fight against Dutch Colonial. This false representation created bad figure of Bahurekso and students cannot take him as role model. This was the colonial agenda to stigmatize Indonesian heroes as bad and to maintain this stigma Dutch colonial hired dalang (shadow puppet masters) to use false Bahurekso story in their performance so that people unconsciously accept the story as truth.